A Gene Expression Screen in Zebrafish Embryogenesis - Kudoh, Tetsuhiro; Tsang, Michael; Hukriede, Neil A.; Chen, Xiongfong; Dedekian, Michael; Clarke, Christopher J.; Kiang, Anne; Schultz, Stephanie; Epstein, Jonathan A.; Toyama, Reiko; Dawid, Igor B. (Genome Research, 2001)
A screen for developmentally regulated genes was conducted in the zebrafish, a system offering substantial advantages for the study of the molecular genetics of vertebrate embryogenesis. Clones from a normalized cDNA library from early somitogenesis stages were picked randomly and tested by high-throughput in situ hybridization for restricted expression in at least one of four stages of development. Among 2765 clones that were screened, a total of 347 genes with patterns judged to be restricted were selected. These clones were subjected to partial sequence analysis, allowing recognition of functional motifs in 163 among them. In addition, a portion of the clones were mapped with the aid of the LN54 radiation hybrid panel. The usefulness of the in situ hybridization screening approach is illustrated by describing several new markers for the characteristic structure in the fish embryo named the yolk syncytial layer, and for different regions of the developing brain.